466 PREVALENCE AND IMPACT OF FRAILTY IN PATIENTS HOSPITALISED WITH COVID-19. THE SALFORD EXPERIENCE IN WAVES 1 AND 2. (14th June 2021) - Khan, A; Espinoza, F R; Kneen, T; Dafnis, A; Allafi, H; Carter, B; Narro-Vidal, M; Short, R; Price, A; Upton, R; Vilches-Moraga, A
Abstract: Introduction: The COVID-19 pandemic has had an extensive impact on the frail older population, with significant rates of COVID-related hospital admissions and deaths amongst this vulnerable group. There is little evidence comparing the prevalence and impact of frailty amongst patients hospitalised with COVID-19 in wave 1 vs wave 2 of the pandemic. Methods: Prospective observational study of all consecutive patients admitted to Salford Royal NHS Foundation Trust (SRFT) between 27th February and 28th of April 2020 (wave 1), and 1st October to 10th November 2020 (wave 2) with a diagnosis of COVID-19. The primary endpoint was in-hospital mortality. Patient demographics, co-morbidities, biochemical parameters, and frailty (using the Clinical Frailty Scale, score 1–4 = not frail, score 5–9 = frail) were collected. A Cox proportional hazards model associating wave and frailty with mortality was used. A logistic regression model was used to associate patient characteristics with wave. Both models adjusted for patient characteristics. Results: A total of 700 patients were included (N = 429, wave 1; N = 271, wave 2). In wave 1, 42% (N = 180) were female; median age was 72; 37% (N = 160) were non-survivors, 49% (N = 212) were frail (CFS 5–9). In wave 2, 38% (N = 104) were female; median age was 73; 30% (N = 80) were non-survivors, 39% (N = 106) were frail. There was a reduction in mortality in wave 2, aHR = 0.71 (95% CI 0.53–0.94). Frailty was associated with increased mortality, after adjustment for age, wave and other patient characteristics. Patients were more frail in wave 1, and the effect of frailty was more pronounced in wave 1 vs wave 2. Conclusion: Frailty is highly prevalent amongst patients of all ages admitted to SRFT with COVID-19. Higher scores of frailty are associated with increased mortality.